Causes of death and mortality in hypertrophic cardiomyopathy patients with implantable defibrillators in Sweden. Issue 7 (July 2016) - Magnusson, Peter; Gadler, Fredrik; Liv, Per; Mörner, Stellan
Abstract : Aims: Implantable defibrillators (ICDs) successfully terminate ventricular arrhythmias in hypertrophic cardiomyopathy (HCM), protect against bradycardia, and monitor atrial arrhythmias. This may alter the natural history and causes of death. Methods: This nationwide observational longitudinal retrospective study of all HCM patients implanted during 1995–2012 obtained data from the Swedish ICD Registry, the National Patient Register, the Cause of Death Register, and were validated by review of medical records. Results: Of 342 patients (mean age 51.8 years, 70.8% males), 45 died during a total follow-up of 1847 years (mean 5.4 years). Mean age at death was 68.2 years (range 21–83 years; 12 were ≥75 years). Mean follow-up time among the deceased was 4.9 years (quartiles 1.4–7.4 years). All-cause mortality was higher in HCM patients compared with the age and sex-matched Swedish general population (standardized mortality ratio 3.4; 95% confidence interval 2.4–4.5; P < 0.001). Main cause of death was heart failure (n = 27), stroke (n = 5), cancer (n = 3), myocardial infarction (n = 2), sepsis (n = 2), and others (n = 4). Two patients died suddenly, one after the ICD was turned off because of inappropriate shocks, and one patient whose device system was removed after infection. HCM was the main cause of death in 76% of the cases, mainly because of progressive heart failure. Conclusion: For HCM patients, ICDs almost eliminate premature arrhythmic death and result in a shift to heart failure as the cause of death in the majority of cases. Still, mortality in HCM patients remains elevated and management of heart failure and comorbidities must be improved to increase survival.